REINSTALL NEW REGISTRATION APPLICATION PROGRAM CUSTOMER ORDINARY TELEPHONE (RESIDENCE) USING MICROSOFT ACCESS SERVICES IN TELECOMMUNICATIONS (YANTEL) PT TELKOM - Reny Lestari; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2002)
To be able to provide services in telecommunications, PT TELKOM establishedTelecommunications Service Center, better known by PUSYANTEL. In its service tothe community there are the constraints faced by the registration system to processpayments. For that reason, this application program is made for the convenience ofprospective customers about the procedures for registration of new pairs of telephoneand telecommunications services provided Services (YANTEL) PT TELKOM can betailored to the needs and demand prospects.